RMT focal plane sensitivity to seismic network geometry and faulting style. Issue 1 (11th April 2016) - Johnson, Kendra L.; Hayes, Gavin P.; Herrmann, Robert B.; Benz, Harley M.; McNamara, Dan E.; Bergman, Eric
Abstract: Modern tectonic studies often use regional moment tensors (RMTs) to interpret the seismotectonic framework of an earthquake or earthquake sequence; however, despite extensive use, little existing work addresses RMT parameter uncertainty. Here, we quantify how network geometry and faulting style affect RMT sensitivity. We examine how data-model fits change with fault plane geometry (strike and dip) for varying station configurations. We calculate the relative data fit for incrementally varying geometries about a best-fitting solution, applying our workflow to real and synthetic seismograms for both real and hypothetical station distributions and earthquakes. Initially, we conduct purely observational tests, computing RMTs from synthetic seismograms for hypothetical earthquakes and a series of well-behaved network geometries. We then incorporate real data and station distributions from the International Maule Aftershock Deployment (IMAD), which recorded aftershocks of the 2010 M W 8.8 Maule earthquake, and a set of regional stations capturing the ongoing earthquake sequence in Oklahoma and southern Kansas. We consider RMTs computed under three scenarios: (1) real seismic records selected for high data quality; (2) synthetic seismic records with noise computed for the observed source-station pairings and (3) synthetic seismic records with noise computed for all possible station-source pairings. To assess RMT sensitivity for each test, we observe the 'fit falloff', which portrays how relative fit changes when strike or dip varies incrementally; we then derive the ranges of acceptable strikes and dips by identifying the span of solutions with relative fits larger than 90 per cent of the best fit. For the azimuthally incomplete IMAD network, Scenario 3 best constrains fault geometry, with average ranges of 45° and 31° for strike and dip, respectively. In Oklahoma, Scenario 3 best constrains fault dip with an average range of 46°; however, strike is best constrained by Scenario 1, with a range of 26°. We draw two main conclusions from this study. (1) Station distribution impacts our ability to constrain RMTs using waveform time-series; however, in some tectonic settings, faulting style also plays a significant role and (2) increasing station density and data quantity (both the number of stations and the number of individual channels) does not necessarily improve RMT constraint. These results may be useful when organizing future seismic deployments (e.g. by concentrating stations in alignment with anticipated nodal planes), and in computing RMTs, either by guiding a more rigorous data selection process for input data or informing variable weighting among the selected data (e.g. by eliminating the transverse component when strike-slip mechanisms are expected).